Modification of foaming properties of soy protein isolate by high ultrasound intensity: Particle size effect - Morales, Rocio (2015)
The effect of high intensity ultrasound (HIUS) may produce structural modifications on proteins through a friendly environmental process. Thus, it can be possible to obtain aggregates with a determined particle size, and altering a defined functional property at the same time. The objective of this work was to explore the impact of HIUS on the functionality of a denatured soy protein isolate (SPI) on foaming and interfacial properties. SPI solutions at pH 6.9 were treated with HIUS for 20 min, in an ultrasonic processor at room temperature, at 75, 80 and 85 °C. The operating conditions were: 20 kHz, 4.27 ± 0.71 W and 20% of amplitude. It was determined the size of the protein particles, before and after the HIUS treatment, by dynamic light scattering. It was also analyzed the interfacial behavior of the different systems as well as their foaming properties, by applying the whipping method. The HIUS treatment and HIUS with temperature improved the foaming capacity by alteration of particle size whereas stability was not modified significantly. The temperature of HIUS treatment (80 and 85°C) showed a synergistic effect on foaming capacity. It was found that the reduction of particle size was related to the increase of foaming capacity of SPI. On the other hand, the invariable elasticity of the interfacial films could explain the stability of foams over time.